Knowledge and Awareness of Medical Certificate of Cause of Death in Medical Undergraduate Students at a Tertiary Care Hospital - Prithiviraja P; Shreeyaa Vijay; M Sreenivasan; Alwin Raj (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: The Medical Certificate of Cause of Death is not just a legal formalitybut the backbone of accurate public health surveillance and policy, yet error rates as high as 50–60% threaten the integrity of national health data and decisionmaking. Addressing persistent gaps in knowledge and practice among medical undergraduates is crucial to ensure reliable mortality statistics and effective healthcare planning for the nation’s future. Objectives: To evaluate medical undergraduates’ knowledge, awareness, and practical competence regarding the purpose, legal signi𿿿cance, correct completion, guidelines, and common errors of the Medical Certi𿿿cate of Cause of Death, andtoidentify gaps in these areas. Materials and Methods: This cross-sectional study was conducted among third year,𿿿nal year, and Compulsory Rotatory Medical Internship (CRMI) students, at Chettinad Hospital and Research Institute using a structured, self-administered online questionnaire to assess knowledge and awareness regarding the Medical Certi𿿿cate of Cause of Death. Data were analyzed with SPSS version 29, and thical approval was obtained from the Institutional Ethics Committee. Results: While all surveyed medical undergraduates correctly identi𿿿ed he xpansion andlegalimportance ofthe MCCD, signi𿿿cant knowledge gaps persisted